Speed of Adjustment to Selected Labour Market and Tax Reforms - Mourougane, Annabelle (OECD Economics Department Working Papers, 2008)
This paper examines the nature and the length of economic adjustments to selected structural reforms, drawing on a variety of approaches: descriptive analysis and simulations using Dynamic General Equilibrium and macro-economic neo-Keynesian models. The descriptive analysis suggests that the correlation between reforms, including a change in the tax wedge, the replacement ratio or anti-competitive product market regulation and the structural unemployment rate peaks only after 5 to 10 years. Lowering employment and price adjustment costs in the euro area to their respective US levels would only have a relatively limited effect on the speed of adjustment to labour market and tax reforms. Monetary policy reaction can speed up the adjustment to a new equilibrium, though to a varying degree in the different OECD countries or regions. In particular, reforms in individual euro area countries are likely to trigger only little or no policy reaction, unless there is an area-wide effort to implement reforms